Diagnóstico da água subterrânea no perímetro urbano de João Pessoa/PB através de índices de qualidade de água - IQAS - Sousa, Beethania Madalow Almeida Anacleto de (2011)
This paper deals with underground water diagnosis of the urban area from João Pessoa, state capital of Paraíba, Brazil, whose aim is evaluate its natural features, over time, considering as one of its main uses its intended, the human provision. For this, it was monitored 13 deep wells (on average 200m) on Beberibe aquifer and spread in urban area from João Pessoa. Such wells belong to water and sewage Company in the state of Paraíba – CAGEPA and present a reliable lithologic profile. It was used the Quality of Water Index from Bascarán – IQAB to evaluate the analytical results. The results demonstrated that during the study period, the water from monitored wells stand, in general, was classified as agreeable on the scale water quality of IQAB. It was found on the physical, chemical and bacteriological individual analysis, ammonia and nitrate levels off limits established by ordinance 518/04 from Health Ministry – Ministério da Saúde/MS. This way, the water classification as agreeable is justified according to IQAB scale. This reality shows the necessity and importance of a major supervision on the ground water on João Pessoa urban area by management agencies to avoid its contamination and, consequently, invalidating the use of this water for human consumption.